T6SS: A Key to Pseudomonas’s Success in Biocontrol? - Edwin D. Navarro-Monserrat; Christopher G. Taylor (Microorganisms, 2023)
Bacteria from the genus Pseudomonas have been extensively studied for their capacity to act as biological control agents of disease and pests and for their ability to enhance and promote crop production in agricultural systems. While initial research primarily focused on the human pathogenic bacteria Pseudomonas aeruginosa, recent studies indicate the significance of type VI secretion (T6SS) in other Pseudomonas strains for biocontrol purposes. This system possibly plays a pivotal role in restricting the biological activity of target microorganisms and may also contribute to the bolstering of the survival capabilities of the bacteria within their applied environment. The type VI secretion system is a phage-like structure used to translocate effectors into both prokaryotic and eukaryotic target cells. T6SSs are involved in a myriad of interactions, some of which have direct implications in the success of Pseudomonas as biocontrol agents. The prevalence of T6SSs in the genomes of Pseudomonas species is notably greater than the estimated 25% occurrence rate found in Gram-negative bacteria. This observation implies that T6SS likely plays a pivotal role in the survival and fitness of Pseudomonas. This review provides a brief overview of T6SS, its role in Pseudomonas with biocontrol applications, and future avenues of research within this subject matter.